Adverse obstetrical and perinatal outcome in adolescent mothers associated with first birth: a hospital-based case-control study in a tertiary care hospital in North-East India - Medhi R; Das B; Das A; Ahmed M; Bawri S; Rai S (Dove Medical Press, 2016)
Robin Medhi, Banani Das, Arpana Das, Mansur Ahmed, Sonika Bawri, Suditi Rai Department of Obstetrics and Gynaecology, Silchar Medical College and Hospital, Silchar, Assam, India Purpose: To analyze the adverse obstetrical and perinatal outcome of adolescent mothers associated with first birth. Patients and methods: This prospective case-control study was conducted in a tertiary care teaching hospital of North-East India between January 2014 and December 2014. All adolescent primigravidae completing 28 weeks of gestation with singleton pregnancy and delivered at our institution were included in the study group. Primigravidae aged between 20 and 25 years were taken as a control group. Mothers having pregnancy complicated with diabetes mellitus, renal disorder, thyroid disorders, and cardiac diseases were excluded from the study. Demographic data, maternal complications like severe anemia, pre-eclampsia, eclampsia, gestational age at delivery, mode of delivery, and postpartum complications were compared. Among fetal complications, low-birth weight, preterm birth, neonatal intensive care unit admission, still birth, and early neonatal death were compared. All the patients were interviewed regarding contraceptive knowledge and its use preceding the pregnancy. Results: Quality antenatal care was received by 80.6% of adolescent mothers. The adolescent mothers had a higher incidence of pre-eclampsia (odds ratio [OR] 2.017 95% confidence interval [CI]: 1.045–3.894, P=0.03), preterm deliveries (OR: 1.655, 95% CI: 1.039–2.636, P=0.03). Among fetal outcomes, the low- birth weight babies (OR: 1.59, 95% CI: 1.016–2.478), low mean birth weight (2,544.4±622.09 g versus 2,701.6±582.51 g), and higher admission to neonatal intensive care unit (OR: 1.957, 95% CI: 1.120–3.417) were significantly associated with adolescent mothers. There was no significant difference found regarding the mode of delivery, still birth, and early neonatal death. Moreover, contraceptive knowledge and its use were found to be poor among adolescent mothers. Conclusion: With quality antenatal, intranatal, and postnatal care, the obstetric risk of childbirth in adolescent mothers may not be as serious as perceived to be. Keywords: teenage, primigravidae, childbirth outcome, contraceptive